Potential ecological risk assessment of heavy metals in surface sediments of Bagmati River, Kathmandu Valley, Nepal (Journal of Nepal Geological Society, 2025)
This study aims to determine the distribution and potential ecological risk of heavy metals and to identify the possible sources of heavy metal contamination in the surface sediments of the Bagmati River in Kathmandu, Nepal. The sediment samples were analyzed for their pH, electrical conductivity (EC), organic matter (OM), texture, and heavy metal concentration of Cu, Zn, Cd, and Pb. Various indices such as contamination factor (CF), geoaccumulation index (Igeo), modified degree of contamination (mCd), pollution load index (PLI), and potential ecological risk index (RI) were calculated to assess the risk of heavy metals. The sediment exhibited a slightly alkaline pH, with significant variation in EC along different river sections. The OM levels were moderate in the upstream and high in the middle and downstream. The sediment was predominantly sandy and loamy sandy in composition. The concentration of Pb was below the limit of detection (